Cerebral Gray Matter Atrophy Is Associated with the CSF IgG index in African American with Multiple Sclerosis. Issue 5 (29th March 2017) - Seraji‐Bozorgzad, Navid; Khan, Omar; Cree, Bruce A.C.; Bao, Fen; Caon, Christina; Zak, Imad; Razmjou, Sara; Tselis, Alexandros; Millis, Scott; Bernitsas, Evanthia
ABSTRACT: BACKGROUND AND PURPOSE: African American (AA) patients with multiple sclerosis (MS) have been reported to have a more aggressive disease course compared to their white counterparts. We explored the relation of gray matter (GM) volume, a marker of tissue injury, and cerebrospinal fluid (CSF) IgG index in both AA and white MS patients. METHODS: This was a cross‐sectional study of 150 self‐identified AA and 150 white patients with MS who underwent magnetic resonance imaging scan of brain and CSF sampling. Intrathecal IgG synthesis was quantified as IgG index. The Spearman test was used for univariate correlation analysis, followed by generalized linear model (GLM) to assess the effect of race on the correlation between IgG index and GM volume. RESULTS: The GM volume was inversely related to the IgG index for the entire group (rho = –.57, P < .0004). The AA group showed a stronger correlation (rho = –.893, P < .00004), as compared to whites (rho = –.019, P = .85), between GM and IgG index. Furthermore, GLM analysis showed a significant effect of race on the relation between IgG index and GM volume ( P < .0005). CONCLUSIONS: AA patients with MS have lower GM volume and a stronger inverse correlation between GM volume and CSF IgG index, compared to the whites. These findings suggest a potentially prominent role of humoral immunity in mediating tissue injury in AA patients with MS.